2018
DOI: 10.12659/pjr.900633
|View full text |Cite
|
Sign up to set email alerts
|

Can Diffusion Weighted Imaging Aid in Differentiating Benign from Malignant Sinonasal Masses?: A Useful Adjunct

Abstract: SummaryBackgroundTo evaluate the role of diffusion weighted imaging (DWI) and apparent diffusion coefficient (ADC) values at 3 Tesla in characterizing sinonasal masses.Material/MethodsAfter ethical clearance, 79 treatment naive patients with head and neck masses underwent magnetic resonance imaging (MRI), including DWI at 3 Tesla using the following b values – 0, 500 and 1000 s/mm2. Thirty-one patients were found to have sinonasal tumours and were subsequently analysed. Image analysis consisted of a morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
3
13
0
1
Order By: Relevance
“…DWI/ADC offers this non-invasive medical intervention. For example, a study by Das et al was reported that 1.791 × 10 − 3 mm 2 /s ADC cut off value in Sinonasal lesions was able to differentiate between benign and malignant lesions with 80% sensitivity and 83.3% specificity [ 24 ]. Barchetti et al in a study of cervical lymph nodes in patients with HNSCC reported a cut off value of 0.965 × 10 − 3 mm 2 /sec to differentiate between benign and malignant nodes with a sensitivity of 97%, a specificity of 93, 92% accuracy, 95% PPV, and 96% NPV of [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…DWI/ADC offers this non-invasive medical intervention. For example, a study by Das et al was reported that 1.791 × 10 − 3 mm 2 /s ADC cut off value in Sinonasal lesions was able to differentiate between benign and malignant lesions with 80% sensitivity and 83.3% specificity [ 24 ]. Barchetti et al in a study of cervical lymph nodes in patients with HNSCC reported a cut off value of 0.965 × 10 − 3 mm 2 /sec to differentiate between benign and malignant nodes with a sensitivity of 97%, a specificity of 93, 92% accuracy, 95% PPV, and 96% NPV of [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that AdCCs have ADC values higher than other malignancies. 17–19 In our cohort, AdCCs had lower ADC values (0.94 × 10 −3 mm 2 /s); this might be explained as most of our cases were high-grade tumors with significant heterogeneously enhancing solid components. 18…”
Section: Discussionmentioning
confidence: 75%
“…9 Previous studies showed that AdCCs have ADC values higher than other malignancies. [17][18][19] In our cohort, AdCCs had lower ADC values Figure 3. Sixty-three year-old female presenting with nasal discharge, with a history of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…The apparent diffusion coefficient (ADC) is sensitive to water molecules in the tissues and reflects the microenvironmental changes of tumors[ 5 ]. It is used to differentiate malignant from benign tumors and to evaluate tumor responses after chemotherapy[ 6 , 7 ]. However, ADC values of the tumor are not consistent after treatment because treatment may cause cell swelling or fibrosis that decreases ADC values[ 8 ].…”
Section: Introductionmentioning
confidence: 99%